2009
DOI: 10.1016/j.cub.2009.06.064
|View full text |Cite
|
Sign up to set email alerts
|

ANXUR1 and 2, Sister Genes to FERONIA/SIRENE, Are Male Factors for Coordinated Fertilization

Abstract: In sexual reproduction, proper communication and cooperation between male and female organs and tissues are essential for male and female gametes to unite. In flowering plants, female sporophytic tissues and gametophytes direct a male pollen tube toward an egg apparatus, which consists of an egg cell and two synergid cells. The cell-cell communication between the pollen tube and the egg apparatus makes the tip of pollen tube rupture to release the sperm cell. To detect male factors involved in this communicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
240
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(253 citation statements)
references
References 17 publications
8
240
1
4
Order By: Relevance
“…For the fast-growing PTs, this growth cessation would lead to a failure in fertilization, necessitating a robust signal transduction network to maintain CW integrity during tip growth. The ANX1/2 RLKs of the CrRLK1L subfamily and their closest homolog FER have been implicated in the control of tip growth in PTs and root hairs, respectively, acting upstream of ROSproducing NADPH oxidases (3,4,19). In this study, we identified MRI, a novel, positive downstream component of these RLK signaling pathways.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…For the fast-growing PTs, this growth cessation would lead to a failure in fertilization, necessitating a robust signal transduction network to maintain CW integrity during tip growth. The ANX1/2 RLKs of the CrRLK1L subfamily and their closest homolog FER have been implicated in the control of tip growth in PTs and root hairs, respectively, acting upstream of ROSproducing NADPH oxidases (3,4,19). In this study, we identified MRI, a novel, positive downstream component of these RLK signaling pathways.…”
Section: Discussionmentioning
confidence: 77%
“…In PTs of the model plant Arabidopsis thaliana, the plasma membrane-localized ANXUR (ANX1 and ANX2) receptor-like kinases (RLKs) play a major role in controlling CW integrity and growth. On one hand, loss of function of the redundant RLKs ANX1 and ANX2 leads to precocious PT rupture shortly after germination, resulting in male sterility (3,4). This phenotype also is seen when the ANX-RLKs are degraded by the endoplasmic reticulumassociated degradation pathway in the turan mutant affecting N-glycosylation (5).…”
mentioning
confidence: 94%
“…Interaction of another related RLK, At2g23200 in yeast two-hybrid assays with the Pseudomonas syringae effector AvrPto showed that its expression was regulated by a number of PAMPs, pathogen-secreted molecules that regulate infection and triggers immunity (Xiang et al 2008). ANXUR 1 and ANXUR 2 which are RLKs help in cell wall integrity and are homologous to FeR, but have opposite functions to FeR (Boisson-Dernier et al 2009;Miyazaki et al 2009). These studies imply a dynamic signaling complex involving FeR and ANXUR.…”
Section: Auxinmentioning
confidence: 99%
“…The CrRLK1L family is conserved in plants and consists of 17 members in Arabidopsis. ANXs are expressed in pollen tubes and loss-of-function of both ANX1 and ANX2 causes precocious pollen tube burst when grown in vitro or in the pistil (Boisson-Dernier et al, 2009;Miyazaki et al, 2009). …”
Section: Rlks Regulate the Integrity Of Pollen Tubesmentioning
confidence: 99%